1990
DOI: 10.7326/0003-4819-112-12-917
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Tumor Necrosis Factor in Severe Alcoholic Hepatitis

Abstract: Elevations in tumor necrosis factor in alcoholic hepatitis are most marked in severe cases, suggesting that tumor necrosis factor plays a role in the pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
166
0
7

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(184 citation statements)
references
References 15 publications
6
166
0
7
Order By: Relevance
“…This includes the correlation beween mortality and plasma levels of TNF-a observed in patients with A allele were cirrhotic compared with 106/137 (77%) TNFA-G homozygotes. Neither this difference nor that between alcoholic steatohepatitis 11,14 and the hepatotoxicity of TNFa shown in various experimental models of liver cell injury. 8 cirrhotics and controls was significant.…”
Section: We Have Examined the Frequency Of The Two Recently De-mentioning
confidence: 97%
See 1 more Smart Citation
“…This includes the correlation beween mortality and plasma levels of TNF-a observed in patients with A allele were cirrhotic compared with 106/137 (77%) TNFA-G homozygotes. Neither this difference nor that between alcoholic steatohepatitis 11,14 and the hepatotoxicity of TNFa shown in various experimental models of liver cell injury. 8 cirrhotics and controls was significant.…”
Section: We Have Examined the Frequency Of The Two Recently De-mentioning
confidence: 97%
“…No differences were observed for the polymoranimal models of alcoholic liver injury. tors have shown increased plasma levels of TNF-a activity in patients with ASH [11][12][13][14][15] and some have shown a correlation In common with other end-organ complications of alcohol with liver function and mortality. 11,14 TNF-a is cytotoxic to abuse, severe liver disease develops in only a minority of sensitized hepatocytes and has been implicated as a proximal heavy drinkers.…”
Section: We Have Examined the Frequency Of The Two Recently De-mentioning
confidence: 99%
“…In addition, endotoxin-induced stimulation of Kupffer cells has been proposed to be an important initiating event leading to the production of proinflammatory cytokines and oxygen free radicals in alcoholic liver disease, which shares histologic similarities with NASH. 30,34,35 On the other hand, Yang et al 14 suggested that systemic endotoxinemia contributes to TNF-␣ production and steatohepatitis in genetically obese rats. Wigg et al 32 found that patients with NASH have a higher prevalence of small-intestinal bacterial overgrowth, the potential source of higher endotoxinemia levels.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, plasma endotoxin levels in alcoholic patients with cirrhosis often do not correlate with circulating levels of proinflammatory cytokines. 44,45 Moreover, 30% to 50% of cases of ALD demonstrate undetectable levels of endotoxin in the plasma. 18,29 The present study presents a clear and important message that the alcoholic liver injury that is associated with LPS exposure may occur in an episodic mode, but in the absence of high, sustained plasma levels of endotoxin.…”
Section: Discussionmentioning
confidence: 99%